Hybrid rice and insect herbivores in Asia - Horgan, Finbarr G.; Crisol, Eduardo (Wiley, 2013)
Since the late 1970s, the area of agricultural land dedicated to hybrid rice has rapidly increased throughout Asia, particularly in China, India, and Vietnam. The pace of hybrid adoption, a generally low genetic diversity of hybrid varieties, and higher agrochemical inputs with hybrid rice compared to conventional varieties has significantly changed the rice landscape. Some authors have associated these changes with an increasing incidence of damage to rice by herbivorous insects. This review examines trends in hybrid adoption in Asia, the associated problems with insect herbivores, and possible solutions to these problems. A series of hypotheses are presented to explain the increased incidence of damage as related to issues of crop susceptibility (hybrid physiology and genetics) and crop vulnerability (management‐related issues). Evidence suggests that hybrid rice has been highly vulnerable to damage from a range of insects. Inadequate attention to issues of planthopper resistance, linked with high agrochemical inputs and a new, vigorous rice type, likely contributed to high levels of planthopper damage in some hybrid rice varieties. Furthermore, hybrid susceptibility to the whitebacked planthopper, Sogatella furcifera (Horváth) (Hemiptera: Delphacidae), has been linked to the female (wild abortive‐cytoplasmic male sterile) parent of some hybrid lines. Meanwhile, a high incidence of stem borer damage to hybrids has likely resulted from the interaction of several plant traits with normal hybrid management, and particularly with the higher fertilizer applications associated with hybrid rice. Despite apparently low levels of resistance, hybrid varieties have high tolerance to herbivore damage; however, aspects of hybrid tolerance have been largely neglected in the literature, in breeding programs, and during development of pest management actions. This review suggests that research into the entomology of hybrid rice needs updating as hybrid varieties and management options continue to change over time. Pest management areas that require further research (including strategies for deployment of resistant varieties) are highlighted and a call is made for increased attention to issues of hybrid tolerance for sustainable herbivore management.